2020
DOI: 10.1039/d0sc03791e
|View full text |Cite
|
Sign up to set email alerts
|

Site-selective aqueous C–H acylation of tyrosine-containing oligopeptides with aldehydes

Abstract: A novel Pd-catalyzed C–H acylation reaction with readily available aldehydes under an aqueous environment towards the assembly of non-protegenic acylated Tyr-containing oligopeptides is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…To evaluate the feasibility of our oxygenation manifold, we first selected the fully protected tyrosine derivative 1 a housing a removable 2‐pyridyloxy group as DG [12b–c,e,14] . After evaluation of the reaction conditions, [15] we observed that the desired acetoxylation event could occur to provide mixtures of mono‐ and diacetoxylated compounds 2 a and 2 a’ , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the feasibility of our oxygenation manifold, we first selected the fully protected tyrosine derivative 1 a housing a removable 2‐pyridyloxy group as DG [12b–c,e,14] . After evaluation of the reaction conditions, [15] we observed that the desired acetoxylation event could occur to provide mixtures of mono‐ and diacetoxylated compounds 2 a and 2 a’ , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As in other Pd‐catalyzed C−H functionalization reactions, the actual role of the silver additive remained unclear, and the authors hypothesized that it could favour either the catalyst regeneration or even any of the elemental steps upon the formation of Ag−Pd heterodimeric species [44] . Encouraged by these results, the same group expanded the synthetic toolbox for the diversification of peptides and reported a robust Pd‐catalyzed radical acylation of a collection of Tyr‐containing peptides with aldehydes [45] . The appendance of a pyridyl group within the oxygen atom of the Tyr ring directed the formation of a 6‐membered palladacycle prone to undergo the corresponding acylation reaction.…”
Section: C−c Bond‐forming Reactionsmentioning
confidence: 99%
“…6 Diverse bioconjugation technologies have been developed to achieve chemo- and site-selective functionalization of natural amino acids (AAs) for the purpose of selective protein modification. 7–20 The low abundance and unique reactivity of the thiol side chain of cysteine (Cys) make it an ideal candidate for bioconjugation chemistry. 21–33 Michael-type addition, nucleophilic substitution and disulfide exchange reaction represent the classical approaches for Cys-selective bioconjugation (Fig.…”
Section: Introductionmentioning
confidence: 99%